Reported a case of water filled bulla in feet (molluscum contagiosum) Water-Filled Bulla in Feet (Molluscum Contagiosum): A Case Study - maryam maghbol; negar azarpira; saeedreza baezzat (Fasa University of Medical Sciences, 2015)
Background & Objectives: Molluscum contagiosum is a benign viral infection of the skin in the genital area of adult patients and children's faces, arms, legs, and trunk. It is spread by direct contact. Lesions are small, flesh-colored, and umbilicated with central cores containing white keratinous material. It is rarely observed in palmar and plantar areas. Case: We present a case of Molluscum contagiosum in the plantar area of a 30-year-old lady as small, painless,nonpruritic  and umbilicated papules in the right. By squeezing lesions cheesy materials were pushed out. The diagnosis was made by excisional biopsy. The patient became asymptomatic by surgical excision and cutherizations. Result: Despite the previous opinion that Molluscum contagiosum is based on the synthesis of new hair follicles and only seen in hairy body, it is in fact a viral infection that can affect the whole surface of the body including palmar and plantar area.